Systematic review and meta-analysis of all randomized controlled trials comparing gynecologic laparoscopic procedures with and without robotic assistance. (October 2021) - Marchand, Greg; Taher Masoud, Ahmed; Ware, Kelly; Govindan, Malini; King, Alexa; Ruther, Stacy; Brazil, Giovanna; Calteux, Nicolas; Coriell, Catherine; Ulibarri, Hollie; Parise, Julia; Arroyo, Amanda; et al.
Abstract: Objective: Following the publication of several high quality randomized controlled trials regarding the comparison of similar laparoscopic gynecologic procedures being performed with or without robotic assistance, we aimed to perform a systematic review to identify any differences in patient safety and expected incidence of complications in these procedures. Data Sources: Articles on ClinicalTrials.Gov, Embase, MEDLINE, PubMed, Scopus, and Web of Science databases were retrieved and screened for eligibility up to April 1st 2021. Methods of Study Selection: In addition to meeting our screening algorithm, we included studies that met all the following: randomized control trials (RCT), enrolling patients for indicated laparoscopic gynecologic procedures, and comparing Robotic Surgery (RS) with Laparoscopic Surgery (LS) in terms of safety or complications. Tabulation, Integration, and Results: Data was pooled as mean difference (MD) or risk ratio (RR) with a 95% confidence interval (CI). Ultimately, six studies were included in this meta -analysis. Pooled data revealed that RS and LS have similar risk for intraoperative complications (RR = 0.87; 95% CI [0.23, 3.36], P = 0.84), postoperative complications (RR = 1.07; 95% CI [0.57, 2.01], P = 0.83), significant intraoperative hemorrhage (RR = 1.40; 95% CI [0.59, 3.34], P = 0.44), postoperative hemorrhage (RR = 0.43; 95% CI [0.15, 1.22], P = 0.11), vaginal cuff dehiscence (RR = 1.13; 95% CI [0.24, 5.41], P = 0.88), postoperative wound infection, urinary tract infection, and urinary bladder or ureteral injury. RS had "surgeon declared" lower estimated blood loss (MD = 85.27; 95% CI [46.45, 124.09], P < 0.00001) and shorter postoperative hospital stay (MD = 1.20; 95% CI [0.38, 2.01], P = 0.004). Conclusion: There was a statistically significant decrease in hospital stay and "surgeon declared" blood loss seen in the RS group. There was no statistically significant increase in risk of developing other postoperative complications between the LS and R groups.